Efficacy of L-dopa in Treatment of Aggression, Frontal Lobe Cognitive Functioning and Task Switching Deficits in Parkinson’s Disease Patients - Gul, Amara; Yousaf, Javed (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To assess efficacy of L-dopa treatment on aggression, frontal lobe and task switching deficits in patients with Parkinson’s disease (PD).Study Design: Prospective comparative study.Place and Duration of Study: Bahawal Victoria Hospital and Civil Hospital Bahawalpur, Pakistan, from Apr 2016 to Oct 2017.Methodology: Seventy-five healthy individuals and seventy-five PD patients participated in the study. This study was completed in two testing sessions. Healthy participants had single testing session whereas patients were tested twice (pre and post L-dopa treatment). Participants completed Frontal Assessment Battery, part B TMT, and Buss-Perry Aggression Questionnaire.Results: PD patients (6.13 ± 0.81) showed deficient frontal lobe functioning F (1,48)=14489.66, p